Hepatitis C Virus RNA-Dependent RNA Polymerase Is Regulated by Cysteine S-Glutathionylation. (3rd September 2019) - Kukhanova, Marina K.; Tunitskaya, Vera L.; Smirnova, Olga A.; Khomich, Olga A.; Zakirova, Natalia F.; Ivanova, Olga N.; Ziganshin, Rustam; Bartosch, Birke; Kochetkov, Sergey N.; Ivanov, Alexander V.
Abstract : Hepatitis C virus (HCV) triggers massive production of reactive oxygen species (ROS) and affects expression of genes encoding ROS-scavenging enzymes. Multiple lines of evidence show that levels of ROS production contribute to the development of various virus-associated pathologies. However, investigation of HCV redox biology so far remained in the paradigm of oxidative stress, whereas no attention was given to the identification of redox switches among viral proteins. Here, we report that one of such redox switches is the NS5B protein that exhibits RNA-dependent RNA polymerase (RdRp) activity. Treatment of the recombinant protein with reducing agents significantly increases its enzymatic activity. Moreover, we show that the NS5B protein is subjected to S-glutathionylation that affects cysteine residues 89, 140, 170, 223, 274, 521, and either 279 or 295. Substitution of these cysteines except C89 and C223 with serine residues led to the reduction of the RdRp activity of the recombinant protein in a primer-dependent assay. The recombinant protein with a C279S mutation was almost inactive in vitro and could not be activated with reducing agents. In contrast, cysteine substitutions in the NS5B region in the context of a subgenomic replicon displayed opposite effects: most of the mutations enhanced HCV replication. This difference may be explained by the deleterious effect of oxidation of NS5B cysteine residues in liver cells and by the protective role of S-glutathionylation. Based on these data, redox-sensitive posttranslational modifications of HCV NS5B and other proteins merit a more detailed investigation and analysis of their role(s) in the virus life cycle and associated pathogenesis.